Malta : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Malta. (IMF Staff Country Reports; Country Report, 2008)
This 2008 Article IV Consultation highlights that Malta has experienced a three-year-long expansion reflecting strong foreign direct investment, export diversification, and value-added upgrading. Financial soundness indicators held up in 2007 despite unfavorable international developments. The banking sector's liquidity and funding profile are healthy, and banks have remained profitable despite markdowns in security portfolios. Nonperforming loans fell further but are still comparatively high and thinly provisioned. The authorities are unbundling and opening to private participation the fuel and gas operations of the public energy company.